CARDIOVASCULAR SUFFERING IN CHILDHOOD OBESITY - Georgiana Russu; Otilia-Elena Frasinariu; Laura Trandafir (Amaltea Medical Publishing House, 2017)
Obesity-related cardiovascular disease is becoming more prevalent in conjunction with the rise in childhood obesity. Children with obesity may exhibit early signs of cardiovascular dysfunction: increased arterial stiffness, early atherosclerosis, changes in the myocardial structure and function. These are the result of their excess adiposity, often independent of other obesity-related comorbidities such as dyslipidemia and insulin resistance. Obesity in childhood predisposes to an increased risk of morbidity and cardiovascular mortality in adult. This review is to highlight the importance and need of programs for early detection, diagnosis, treatment and prevention of childhood obesity in order to decrease the incidence of the cardiovascular pathology in adults.